Single Nucleotide Polymorphism of Follicle Stimulating Hormone Receptor Gene in Iraqi Infertile Men - Randa Rasool Ghmayes1, Abdul Kareem A.Alkazaz1, Ahmed Adnan A.Rasool2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The study was directed to determine Single Nucleotide Polymorphism (rs6166 A>G) of follicle stimulating hormone receptor gene and their association as a risk factor with male infertility in Iraqi sterile patient. In the present study after seminal and serum analysis 50 patient (25 Azoospermia and 25 oligozoospermia) and 50 healthy fertile control were joined. The samples were collected from the Biotechnology Department/college of science/Baghdad university and Kamal Al-Samarie IVF Hospital, Baghdad, Iraq. through the period of two months from November 2018 to January 2019. The SNP (rs 6166) determination was carried out by using real-time polymerase chain reaction (qPCR) of blood samples. The difference in the mean of genotype showed a significantly different (p<0.05) in infertile patients group likened to corresponding means infertile control group. Survey of follicle stimulating hormone receptor gene SNP genotypes and allele frequencies in Azoospermia and oligozoospermia patient groups with the control group, showed that there was a significant variation in the heterozygous (AG) and homozygous mutant (GG) genotype frequencies in (rs 6166). It concluded that this SNP may have a role in an Azoospermia and oligozoospermia Iraqi patients complaining from idiopathic infertility.